2018
DOI: 10.1039/c8ra01898g
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and targeting potential assessment of mucoadhesive chitosan nanoparticles designed for ulcerative colitis via scintigraphy

Abstract: aIn the present investigation we have prepared and characterized curcumin (CN)-containing chitosan nanoparticles (CS-NPs) coated with Eudragit FS 30D for colon-specific drug delivery for treatment of ulcerative colitis. Methods: CS-NPs were prepared by ionic gelation using tripolyphosphate. To specify pH sensitive delivery, CS-CN-NPs were coated with Eudragit FS 30D by using a solvent evaporation method. Different process parameters were evaluated, and the optimized formulation was characterized by particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Other options such as chitosan, a chitin derivative, have been shown to increase epithelial permeability by affecting TJs. When formulated as a cationic coating for nanostructured lipid carriers, researchers have observed increased delivery across a membrane and stronger pharmacological response [ 75 , 76 , 77 ]. Given the constrictions imposed by mucus on the types of drugs, this can provide a broad range of drugs access to this administration route.…”
Section: Factors Affecting Intranasal Drug Deliverymentioning
confidence: 99%
“…Other options such as chitosan, a chitin derivative, have been shown to increase epithelial permeability by affecting TJs. When formulated as a cationic coating for nanostructured lipid carriers, researchers have observed increased delivery across a membrane and stronger pharmacological response [ 75 , 76 , 77 ]. Given the constrictions imposed by mucus on the types of drugs, this can provide a broad range of drugs access to this administration route.…”
Section: Factors Affecting Intranasal Drug Deliverymentioning
confidence: 99%
“…They found that the mucoadhesive property of chitosan allowed these NPs to predominantly accumulate in the intestinal mucosa with a gastric retention time of 8 h and the majority of radioactivity observed in the colon after 24 h. There was minimal systemic absorption and accumulation in internal organs [146]. Similarly, colon-targeted curcumin-loaded chitosan NPs coated with Eudragit FS 30D were found to retain highly in the colon with little accumulation in other organs [147]. Navarro et al reported less than 1% accumulation of chitosan NPs in the spleen, liver, kidneys, heart, lungs, and brain after oral administration of fluorescent tagged FITC-PLGA-chitosan NPs daily for 7 days and attributed these findings to chitosan's mucoadhesive properties and the rapid elimination from the systemic circulation [148].…”
Section: Effect Of Mucosal Routes Of Administrationmentioning
confidence: 99%
“…In vivo distribution revealed good accumulation of chitosan nanoparticles in the colonic region. 24 Histone particles showed high positive surface charge (+24.6 ± 1.7 mV), as shown in Figure S2. Critically, histone exhibited strong mucoadhesion properties, and it showed 23.9 ± 0.5% binding to excised rat colon, whereas the negatively charged albumin nanoparticles showed only 2.3 ± 1.3% (Figure 2I).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Similarly, curcumin loaded chitosan nanoparticles were prepared by ionic gelation and solvent evaporation method. In vivo distribution revealed good accumulation of chitosan nanoparticles in the colonic region . Histone particles showed high positive surface charge (+24.6 ± 1.7 mV), as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 92%